Impact of 1h oral glucose tolerance test on the clinical status of adult cystic fibrosis patients over a 4-year period. - Valérie Boudreau; Quitterie Reynaud; Angélique Denis; Johann Colomba; Sandrine Touzet; Katherine Desjardins; Stéphanie Poupon Bourdy; Isabelle Durieu; Rémi Rabasa-Lhoret (PLoS ONE)
Objective To report the clinical profile associated with G60 and I60 over a 4-year prospective observational period in 2 large cohorts of adult patients with CF. Methods 319 patients were included (210 Canadian and 119 French) and classified according to their inclusion G60 (≥ or < 11.1 mmol/L) and the median inclusion I60 (≥ or < 24 mU/I). Forced expiratory volume in 1 second (FEV1), body mass index (BMI) were collected on OGTT days. Linear mixed regression models were used to assess the effect of G60 and I60. Results High G60 was not associated to a lower FEV1 at inclusion and the follow-up decline was not higher in the high G60 group (Coefficient [95% CI]: -3.4 [-7.4;0.6], p = 0.0995.). There was no significant association between BMI and G60. Patients with high I60 tended to have a higher mean BMI (+0.5 kg/m2 [0.0 to 1.1], p = 0.05) but no interaction over time was observed. Conclusions High G60 is not associated with a lower lung function at inclusion nor its decline over a 4-year follow-up. High I60 is slightly associated to a higher weight at inclusion, but not with BMI evolution over time in adult patients.